(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2023)
Today, innovative pedagogical technologies are considered as the most effective tools in the educational process. They are widely used in world foreign language teaching practice. Not all active learning methods are interactive methods. When we say interactive teaching methods, first of all, the method of learning and mastering the subject among students is based on mutual communication. This article discusses the use of interactive methods in English language classes.